Effects of Rhizobacteria Inoculation on Germination and Physiology Status of Tomato under Salt Stress - Khaled, Boufares; Mostefa, Kouadria; Naima, Merdjet Yahia; Abdelwahab, Benali (Annals of Arid Zone, 2022)
The aim of this work is to explore the effect of inoculation with nativerhizobacteria strains isolated from steppe ecosystems on enhancing salt tolerance oftomato (Solanum lycopersicum L.). For this purpose, various rhizobacteria strains havebeen purified, identified, and then applied on tomato seeds, in vitro then in potsto study their effects on the germination parameters and growth under salt stress.Eight genera of rhizobacteria strains were identified; they displayed pertinent plantgrowth promotion features such as phytohormones biosynthesis, fixation of atmosphericnitrogen, and phosphate solubilization. The obtained results demonstrated that salinitynegatively affected seed germination and impaired plant growth. In response to saltstress, uninoculated plants accumulated a significant amount of osmoregulators (prolineand glycine betaine), and recorded a decrease in their chlorophyll content, compared toinoculated plants, where the salinity tolerance has been much better with a high seedlinggrowth as well as high chlorophyll and low osmolyte contents. Among the eight strainsused in this study, three (Agrobacterium, Citrobacter and Enterobacter) demonstrated theireffectiveness in enhancing salt tolerance of tomato plants. The use of native rhizobacteriastrains as biofertilizer could be a sustainable approach to improve plant growth insalinity-impacted regions.